Multidimensional internet use related to cognitive performance in older persons: a nationwide cross-sectional study - Fan, Yue; Wei, Hua; Tao, Qunshan (Frontiers in Public Health, 2024)
IntroductionThe internet has been increasingly recognized as a potential driver for enhancing cognitive functioning in older adults; however, the mechanisms underlying this relationship remain insufficiently understood in the literature. This study aimed to investigate the associations between different dimensions of internet use—activity, device, and frequency—and cognitive performance in older adults.MethodsThis cross-sectional study utilized data from the fourth wave of the China Health and Retirement Longitudinal Study (CHARLS), involving a nationally representative sample of 17,676 participants aged 60 years and above. Multiple linear regression analyses were conducted to explore the relationship between MIU and cognitive ability. To explore the moderating effect of age on the relationship between internet use and cognitive functioning, the population was divided into upper (over 75 years) and lower (under 75 years) age groups.ResultsThe analysis revealed a significant positive association between internet use and cognitive function. Specifically, MIU were found to contribute positively to cognitive performance. Subgroup analyses showed that participants aged 60–75 years benefited more from internet use, whereas those over 75 years exhibited a weaker association, indicating a potential decline in the cognitive benefits with advancing age.ConclusionAccording to the results of the present study, MIU significantly increased the cognitive ability of older adult individuals. Additionally, MIU strongly influences components of cognitive functioning, including language, attention, calculation ability, orientation, memory. However, aging may weaken the relationship between MIU and cognitive ability.